Salt effects on mixed composition membranes containing an antioxidant lipophilic edaravone derivative: a computational-experimental study. Issue 29 (13th July 2022) - Laudadio, Emiliano; Minnelli, Cristina; Mobbili, Giovanna; Sabbatini, Giulia; Stipa, Pierluigi; Rusciano, Dario; Galeazzi, Roberta
Abstract : The protection of lipid membranes against oxidation avoids diseases associated with oxidative stress. Abstract : The protection of lipid membranes against oxidation avoids diseases associated with oxidative stress. As a strategy to contrast it, functionalized lipids with antioxidant activity are used to become part of membranes thus protecting them. For this purpose, a lipophilic edaravone derivative has been synthesized, adding a C18 saturated chain to the original structure. The antioxidant activity of C18-Edv has been demonstrated in our previous work. In this study, molecular dynamics simulations have been performed to define the effects of NaCl, MgCl2, KCl, and CaCl2 salts on a palmitoyl-oleoyl- sn -glycero-phosphocholine (POPC) lipid bilayer encapsulating C18-Edv. The results showed how different salts influence POPC lateral diffusion, and the movements of C18-Edv heads, which are antioxidant moieties, were correlated to the ability of C18-Edv molecules to protect membranes. MgCl2 showed a negative impact leading to C18-Edv clusterization and membrane stretching, while KCl and NaCl showed a moderate influence on the mixed lipid membrane structure. CaCl2 increased the exposure of the C18-Edv heads to the lipid–water interface, resulting in the salt with a higher propensity to guarantee protection against radicals in the aqueous phase. Finally, C18-Edv-POPC liposomes have been prepared following the simulation conditions, and then an experimental Oxygen Radical Absorbance Capacity (ORAC) assay has been performed to confirm the in silico predicted results.